Werther at Work: Intra-Firm Spillovers of Suicides - Martin Halla; Bernhard Schmidpeter (Institute of Labor Economics (IZA), 2024)
Suicide is a leading cause of death worldwide and a critical public health concern. We examine the hypothesis of suicide contagion within in the workplace, investigating whether exposure to a coworker's suicide increases an individual's suicide risk. Using high-quality administrative data from Austria and an event study approach, we compare approximately 150,000 workers exposed to a coworker's suicide with a matched group exposed to a "placebo suicide". We find a significant increase in suicide risk for exposed individuals, with a cumulative treatment effect of 0.04 percentage points (33.3 percent) over a 20-year post-event period. Exposed individuals who also die by suicide are more likely to use the same method as their deceased coworker, strongly suggesting a causal link. Two placebo tests bolster this interpretation: workers who left the firm before the suicide and those exposed to a coworker's fatal car accident do not show an elevated suicide risk.
Keywords: I10; I12; I18; D81; J10; 330; suicide; workplace; contagion hypothesis; Werther-effect; mental health